Identification of Hypoxia-Related Subtypes, Establishment of Prognostic Models, and Characteristics of Tumor Microenvironment Infiltration in Colon Cancer - Wang, Changjing; Tang, Yujie; Ma, Hongqing; Wei, Sisi; Hu, Xuhua; Zhao, Lianmei; Wang, Guiying (Frontiers in Genetics, 2022)
Background: Immunotherapy is a treatment that can significantly improve the prognosis of patients with colon cancer, but the response to immunotherapy is different in patients with colon cancer because of the heterogeneity of colon carcinoma and the complex nature of the tumor microenvironment (TME).In the precision therapy mode, finding predictive biomarkers that can accurately identify immunotherapy-sensitive types of colon cancer is essential.Hypoxia plays an important role in tumor proliferation, apoptosis, angiogenesis, invasion and metastasis, energy metabolism and chemotherapy and immunotherapy resistance.Thus,understanding the mechanism of hypoxia-related genes(HRGs) in colon cancer progression and constructing hypoxia-related signature will help enrich our treatment strategies and improve patient prognosis.Method :We obtained the gene expression data and corresponding clinical information of 1025 colon carcinoma patients from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) databases, respectively.We identified two distinct hypoxia subtypes（subtype A and subtype B）according unsupervised clustering analysis and assessed the clinical parameters, prognosis, and TME cell infiltrating characteristics of patients in the two subtypes.We identified 1132 differentially expressed genes (DEGs) between the two hypoxia subtypes and all patients were randomly divided into the training group(n=513) and testing groups(n=512).The level of immune checkpoint related genes and TIDE score were significant lower in subtype A than in subtype B ,indicating the subtype A might benefit from immune checkpoint inhibitors .Finally, a HRG-score signature for predicting prognosis was constructed through the training group and the the predicitive capability was validated through the testing group.The survival analysis and correlation analysis of clinical parameters revealed the prognosis of patients in the high risk group was significantly worse than those in the low risk group.There were also significant differences in immune status, mis-match repair status(MMR ), cancer stem cell index(CSC), between the two risk groups. The correlation analysis of risk scores with IC50 and IPS showed that patients in the low-risk group had a higher benefit from chemotherapy and immunotherapy. than those in the high-risk group,and the external validation IMvigor 210 demonstrated the patients with low risk were more sensitive immunotherapy.